A case report of Wegener granulomatosis (WG) presenting epistaxis, hemoptysis and polyarthralgia - Buklioska Ilievska, Daniela; Volkanovska Ilijevska, Cvetanka; Kuzmanovska Dimitrovska, Melina (Slovenian Respiratory Society, 2020)
Background: Wegener granulomatosis (WG) is a rare multisystem autoimmune disease characterized by necrotizing granulomatous inflammation, tissue necrosis, and vasculitis in small and medium-sized blood vessels. The classic clinical pattern is a triad involving the upper airways, lungs and kidneys. Case presentation: A 33-year-old woman was admitted to our hospital with a history of progressively worsening dry cough, shortness of breath, polyarthralgia, fever, epistaxis and hemoptysis. Two months before admission, she had episodes of nasal bleeding, dry cough, fever not more than 38.2°C. Her primary physician did not detect any abnormal findings in the chest radiographs at that time. Two months later, she consulted the doctor again due to the symptoms and because of the chest X-ray with multiple small infiltrates in both lungs, high sedimentation rate she was admitted to our hospital. Lungs were clear to auscultation bilaterally. Laboratory results revealed anemia with Hgb 90g/L, hematocrit 30%, erythrocytes 3600/L, leucocytes 13800/L, CRP 110mg/L, sedimentation rate 70mm/h. Urine sediment – erythrocytes 16-18, proteins +, epithelial cells ++. 24hour proteinuria 0,5g/L (upper limit 0,2). Rheumatoid antibodies: positive c-ANCA 95U/ml, RF 158IU/ml, ASO 88U/ml. ECG with sinus tachycardia of 120 beats/min. Gas analyses in partial respiratory failure with hypoxemia 7,5kPa and hypocapnia 3,6kPa, oxygen saturation 91%. Chest radiography and lung CT showed multiple infiltrates in the bilateral upper lobes. Bronchoscopy finding of intranasal coagulum without changes of nasal mucosa, transoral intubation revealed diffuse erythema and edema of the vulnerable tracheobronchial mucosa without any ulcerous lesions or infiltrative changes. Chest ultrasound with many apical bilateral, subpleural, hypoechogenic changes with zones of central necrosis with maximal diameter 20mm. Ophthalmology examination - punctiform conjunctival bleeding. Transbronchial biopsy was performed and revealed necrotic granulomas with multinucleated giant cells in the bronchial/bronchiolar and parenchymal lesions. Bronchial alveolar lavage (BAL) was performed and showed the small increase of neutrophils (total cell counts: 320/μL, neutrophils: 19.2%, macrophages: 85.0%, lymphocytes: 7.4%, eosinophils: 0.0%) and no growth of bacterial culture. According to the results the diagnosis granulomatosis with polyangiitis, Wegener’s granulomatosis. She was successfully treated by rheumatologist with high-dose steroids and cyclophosphamide. Conclusion: The recognition of multisystem disease involving joints, kidney, eye and lung is critical for diagnosing Wegener's vasculitis.
Keywords: Wegener granulomatosis